Profiles of Learning Models and Media While Online Study During the Covid-19 Pandemic: A Literature Review - Iqbal Ainur Rizki; Hanandita Veda Saphira; Nina Fajriyah Citra (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2022)
The Covid-19 pandemic has had a major impact on education in Indonesia. Therefore, teachers need to build a learning system using media and learning models following current pandemic conditions. In this regard, the study is focused on analyzing effective learning models and media to provide their advantages and disadvantages when used during online learning so that teachers can choose a learning system that suits students' needs and conditions. This research uses literature study methods with qualitative descriptive analysis. There are 12 journals that have been successfully obtained and reviewed from the title, research results, and conclusions. The findings showed that suitable online learning models are student-centered learning models such as PjBL, PBL, DL, ORNE, Cooperative TGT, and guided inquiry. In addition, the use of ICT-based interactive media can improve learning outcomes, motivation and creativity of learners, also support the implementation of online learning well.